Perlukah Guru BK Memberitahu Batas Kerahasiaan pada Sesi Awal Konseling? - Maulidina, Dinda Aulia Putri; Salsabila, Faiza; Alika, Alya; Grahita, Catur; Syifa , Nida (Jurnal Inovasi Global, 2025)
The introduction of the principle of confidentiality and the application of the limits of confidentiality in practice as an important part of education and is part of the responsibility of counseling teachers. This research uses quantitative and qualitative descriptive analysis methods, the informants of this research are teachers by observation and distributing questionnaires to 30 counseling teachers. The statement regarding the counseling teacher/counselor does not need to tell students during the initial counseling session about the boundaries of confidentiality stated that there were 7 people who disagreed or around 23%, and those who answered strongly disagreed were 10 people or around 33%. Confidentiality limits need to be implemented so that students feel trusted and their rights are respected, for example, such as telling what students can and cannot tell during counseling sessions and maintaining the confidentiality of information conveyed by students. Therefore, it can be concluded that the principle of confidentiality and the application of confidentiality limits are quite important and become an asset for counseling teachers/counselors in carrying out their duties.